South China Sea – A Multifaceted Conflict - Behrendt, Paweł (Power Shifts in East Asia and Their Implications for Asia–Europe Relations, 2019)
Forming the maritime heart of SE Asia, the South China Sea has grown in recent years into one of the most important geopolitical areas in the world. The conflict over seemingly insignificant archipelagos has many aspects, and, like a lens, focuses the rivalry of modern powers. The territorial dispute over the Spratly and Paracel Islands is the primary level of conflict, with prestigious and economic meaning. Another aspect is the striving for control over the regional Sea Lanes of Communication. The point here is not only the transport of goods from east Asia to Europe and Africa, but also of oil and natural gas supply from the Persian Gulf. The next aspect is related to Sino-American relations and rivalry. An equally important facet is the internal politics of the PRC, which is one of the causes of an assertive foreign policy. The CPC has become hostage to its own nationalist rhetoric. There is also a broader international level of the dispute. Countries such as Australia, India and Japan have to a greater or lesser extent joined the conflict as an element of their China policy. The South China Sea unexpectedly found its place in Russian-Chinese relations, and interest in the situation in the region is also expressed by France and the United Kingdom. All these aspects form an image of a very complex and dynamic conflict of growing importance.